Chinese Guideline for Diagnosis and Treatment of Human Immunodeficiency Virus Infection/Acquired Immunodeficiency Syndrome (2024 Edition) - Acquired Immunodeficiency Syndrome Professional Group of Society of Infectious Diseases, Chinese Medical Association; Chinese Center for Disease Control and Prevention (Xiehe Yixue Zazhi)
In 2005, the Acquired Immunodeficiency Syndrome Professional Group of Society of Infectious Diseases, Chinese Medical Association formulated the "Guideline for Diagnosis and Treatment of AIDS" in China (hereinafter referred to as the "Guideline"). The 2024 edition of the Guideline is revised based on the 5th edition in 2021, with reference to the latest research progress at home and abroad. The new edition focuses on updates to antiviral therapy, comprehensive management, opportunistic infections, human immunodeficiency virus (HIV) infection complicated with tumors, prevention and intervention of HIV infection, and newly introduces the section on "immunological non-responder (INR) in AIDS", which for the first time proposes the concept of "vulnerable populations with AIDS", and provides recommendations for diagnosis and treatment, as well as evidence and strength of the recommendations. The new edition covers epidemiology, etiological characteristics, laboratory testing, pathogenesis, clinical manifestations and staging, diagnostic criteria, common opportunistic infections, antiviral therapy, immune reconstitution inflammatory syndrome, INR, AIDS-related tumors, prevention of mother-to-child vertical transmission of HIV and fertility in single-positive families, pre- and post-exposure prophylaxis and interruption of HIV infection, comprehensive management of HIV infection, etc. It aims to assist clinicians in making rational decisions in the diagnosis, treatment, and management of AIDS. It will also be regularly revised and updated according to research progress at home and abroad.